Like” and “Love” Responses as Addiction Factors on Social Media - Mega Putri Alifa; Miskatyas Putri Aransih; Diah Ayu Aguspa Dita; Rizki Edmi Edison (International Conference of Mental Health, Neuroscience, and Cyber-psychology)
The discovery of internet has facilitated humans in their daily life such as in getting information, performed business transaction, etc. The occurence of social media since the 1990s has developed a new function of internet which enables the users to interact with each other virtually. Unfortunately, social media is suspected to cause phubbing behavior among internet users. A previous study has stated that the ‘like’ and ‘love’ responses in social media posts may cause a social media addiction in the users’ everyday life that can interfere with their daily activities. In this article, we explain briefly a review from neuroscience perspective on the emergence of addictive behavior in the use of social media in daily life.